1992
DOI: 10.1080/01688639208402838
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cognition in Alzheimer's disease: Subtypes of global-local impairment

Abstract: This study investigated whether subgroups of AD patients exhibit different patterns of impairment in analyzing global (configural) and local (detail) features of complex visual stimuli. A High Spatial AD subgroup (i.e., patients with better block constructions than naming) and a High Verbal AD subgroup (i.e., patients with better naming than block constructions) were impaired in analyzing both global and local forms. As predicted, however, the High Spatial AD patients exhibited greater impairment in analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 27 publications
5
36
0
Order By: Relevance
“…More specifically, the relatively greater impairment of global than local pitch pattern analysis in typical AD and the similar profile in LPA corroborate our experimental predictions. Impaired global processing of pitch information in music is in line with other evidence for defective formation of coherent global stimulus representations in AD: this deficit might reflect increased demand for coordinated integrative computations between temporo-parietal association cortices vulnerable to Alzheimer pathology [81][82][83][84][85], though any disadvantage with respect to the coding of local stimulus features is likely to be relative rather than absolute [37][38][39][40]86]. While the processing of global stimulus characteristics unfolding over longer time windows requires attentional resources [40,82,86], it is unlikely that the profile of pitch deficits here was entirely underpinned by attentional compromise: as our paradigm required a single response to consecutively presented stimuli, it is unlikely to have taxed divided attention, while demands on sustained attention are likely to have been similar in the timbral deviance detection task, on which the present AD group performed normally.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…More specifically, the relatively greater impairment of global than local pitch pattern analysis in typical AD and the similar profile in LPA corroborate our experimental predictions. Impaired global processing of pitch information in music is in line with other evidence for defective formation of coherent global stimulus representations in AD: this deficit might reflect increased demand for coordinated integrative computations between temporo-parietal association cortices vulnerable to Alzheimer pathology [81][82][83][84][85], though any disadvantage with respect to the coding of local stimulus features is likely to be relative rather than absolute [37][38][39][40]86]. While the processing of global stimulus characteristics unfolding over longer time windows requires attentional resources [40,82,86], it is unlikely that the profile of pitch deficits here was entirely underpinned by attentional compromise: as our paradigm required a single response to consecutively presented stimuli, it is unlikely to have taxed divided attention, while demands on sustained attention are likely to have been similar in the timbral deviance detection task, on which the present AD group performed normally.…”
Section: Discussionsupporting
confidence: 73%
“…However, the effects of these diseases on more complex pitch pattern processing have not been resolved. Studies in the visual domain suggest that patients with AD may have disproportionate difficulty in the analysis of global structure with relatively intact analysis of local features: this profile is likely to reflect dysfunction of integrative mechanisms in parietal cortex that are particularly targeted by AD pathology but may be more difficult to interpret in the context of associated executive, verbal or spatial deficits [37][38][39][40][41][42][43]. In the musical domain, it follows that AD should produce more severe impairment for processing global (melody contour) than local (pitch interval) patterns; whereas in PNFA, a more pervasive impairment of local and global pitch pattern processing would be anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown atypical asymmetries in mesial temporal and parietal regions in individuals at risk for AD (Reiman, Caselli, Yun, Chen, et al, 1996;Small et al, 1995;Soininen et al, 1994). Findings of lateralized cognitive profiles in at-risk individuals also are consistent with the asymmetric neuropsychological profiles identified in mildly demented patients with AD (Albert et al, 1990;Delis et al, 1992;Demadura et al, 2001). The lateralized cognitive deficits noted in these studies presumably reflect lateralized onset in AD with asymmetric changes likely to present in temporoparietal regions (Franceschi et al, 1995;Grady et al, 1990;Haxby et al, 1990).…”
Section: Discussionsupporting
confidence: 56%
“…Some of the participants were recruited through advertisements and others were family members and spouses of AD patients who were being followed at the ADRC. We conducted a retrospective analysis of all individuals who had completed both the Digit Span and Visual Memory Span subtests as part of their full neuropsychological examination (see Salmon & Butters, 1992). There were 23 eligible participants with at least one ApoE-e4 allele (e4+ group), but two individuals (both ε3/ε4 genotype) were excluded because they performed below a cut-off for cognitive impairment of 130 points based on the Mattis Dementia Rating Scale (DRS) (Monsch, Bondi, Salmon, Butters, et al, 1995).…”
Section: Methods Participantsmentioning
confidence: 99%
“…However, more detailed studies using cognitive neuroscience paradigms have further refined our knowledge of the component processes involved in cognitive asymmetry. Delis et al (1992) suggested that the traditional verbal/spatial dichotomy could mask a more primary impairment in processing large, global forms relative to detailed, local stimuli. Subsequent studies using computerized global/local (Navon-type) visual stimuli identified specific impairments in disengaging and shifting attention (Filoteo et al 1992) in early AD, possibly resulting from disconnection of posterior temporoparietal regions (Parasuraman et al 1992).…”
Section: Cognitive Discrepancy Studiesmentioning
confidence: 99%